The Tripoint of Civilisations – Anatolia During the Campaigns of Lucius Licinius Lucullus (74–66 B.C.E.) - Jastrząbek, Jakub (Vade Nobiscum, tom XXIV/2024: Studia nad Bliskim Wschodem, 2024)
Anatolia was an area of the clash of three cultures: Roman, Greek and Eastern. This issue is exceptionally well visible in an analysis of the Third Mithridatic War which was a resolution of a battle for domination in the region lasting over a half of century. The Romans’ general was Lucius Licinius Lucullus, educated nobilis and philhellene; he fought against Mithridates VI, a despotic ruler of Pontus, who was later aided by the king of Armenia Tigranes II. Over the course of the discussed campaigns (and the previous decades) the members of three cultures enter conflicts. At the same time, examples of these groups cooperating can be found, which herald their future reconciliation.